Substituting conventional steel alloys by carbon fibre composites in structural parts of an existing laser cutting equipment - Vieira, D. G. (2011)
In the present work, Finite Element Analysis (FEM) was employed to validate the use of advanced carbon fibre composites as replacement of traditional low-alloy steel in the construction of the main runway frame structure of a laser cutting equipment currently available in the market. This new composite solution was adopted to increase considerably the current laser equipment precision and cutting speed. The main objective is to enhance the machine cutting performance by using much stiffer and lighter main structural runway frames to support the machine cutting head and all major laser beam mirrors and lens, which allows decreasing dramatically the inertial and vibration efforts developed in service through the use of carbon fibre composites. The paper will present, compare and discuss the mechanical and dynamical behaviour obtained in the FEM simulations made by using both solutions, the current one based on a steel frame and the new innovative composite adopted structure. The processing method to be used in the production of the innovative composite structure will be also proposed. Finally, as production costs may also have an important impact on final equipment commercial price and acceptation, an economical study considering both manufacturing situations (currently used and new one) will be discussed.